Alpinia laosensis, the correct name for a species previously misidentified as A. conchigera - Ye, Xing-Er; Nguyen, Khang Sinh; Souvannakhoummane, Keooudone; Nguyen, Quoc Binh; Chen, Juan (Phytotaxa, 2021)
Alpinia laosensis was previously placed in synonymy under A. conchigera. However, a critical examination of herbarium specimens (including type material) and living plants of A. laosensis and A. conchigera reveals that they are two separate species. Alpinia laosensis can be distinguished from A. conchigera by the shape of its fruits, shape and size of leaves and colour of labellum. We therefore reinstate A. laosensis as an independent species. A detailed description of A. laosensis together with a distribution map of both species are provided.